A transnacionalidade de artista no Museu Afro Brasil : Yonamine e José Pedro Croft - Marcondes, Neide (2017)
In today’s world artists narrate history / work in the various modes of expression. The interpretation / reading proposal of the poetics of contemporary artists, Yonamine and José Pedro Croft, who participated in the Portugal Portugueses exhibition at the Afro Museum in São Paulo. The focus of the research was to analyze if the aesthetic universe of installation arts are products of globalization, to verify if the transnationality is present in the artistic product